PELATIHAN EXCELLENT SERVICE DALAM MENINGKATKAN SUMBER DAYA MANUSIA (SDM) FOOD & BEVERAGE (F&B) PADA KARYAWAN DI SEMARANG ROYAL GOLF - Ahmad Mansur; Syamsul Hadi; Umar Abdul Jabbar (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Service is the main and first key for the comfort of guests who come to a company, Service Excellence is the key. In language Service Excellence consists of two words, namely Service and Excellence. Every activity that is intended and intended to provide satisfaction through services provided by someone satisfactorily, something that is provided is of high quality and exceeds what the customer expects. the quality of Human Resources (HR) of employees in restaurants needs to be improved. One way to improve the quality of service for employees is for employees to be given direction and training regarding the importance of excellent service. Excellent service is an effort to provide a sense of satisfaction and foster trust in or customers in food and beverage business managers